Salbutamol transport and deposition in healthy cat airways under different breathing conditions and particle sizes - Fernández-Parra, Rocio; Pey, Pascaline; Reinero, Carol; Malvè, Mauro (Frontiers in Veterinary Science, 2023)
Salbutamol is a bronchodilatator commonly used for the treatment of feline inflammatory lower airway disease, including asthma or acute bronchospasm. As in humans, a pressurized metered dose inhaler (pMDI) is used in conjunction with a spacer and a spherical mask to facilitate salbutamol administration. However, efficacy of inhalation therapy is influenced by different factors including the non-cooperative character of cats. In this study, the goal was to use computational fluid dynamics (CFD) to analyze the impact of breathing patterns and salbutamol particle size on overall drug transport and deposition using a specific spherical mask and spacer designed for cats. A model incorporating three-dimensional cat airway geometry, a commercially available spherical mask, and a 10cm spacer, was used for CFD analysis. Two peak inspiratory flows were tested: 30 mL/s and 126 mL/s. Simulations were performed with 30s breathing different inspiratory and expiratory times, respiratory frequencies and peaks. Droplet spray transport and deposition were simulated with different particle sizes typical of the drug delivery therapies (1, 5, 10 and 15 µm). The percentage of particle deposition into the device and upper airways decreased with increasing particle diameter during both flows imposed in this cat model. During increased mean ventilatory rate (MVR) conditions, most of the salbutamol was lost in the upper airways. And during decreased MVR conditions, most of the particles remained in suspension (still in hold-up) between the mask and the carina, indicating the need for more than 30 seconds to be transported. In both flows the percentage of particles travelling to the lung was low at 1.5-2.3%. In conclusion, in contrast to what has been described in the human literature, the results from this feline model suggest that the percentage of particles deposited on the upper airway decreases with increasing particle diameter.